Hubungan Board Gender Diversity dan Capital Intensity Terhadap Agresivitas Pajak - Amalia, Dina (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2024)
The aim of this study is to determine the effect of capital intensity on tax aggressiveness and board gender diversity in moderating the effect of capital intensity on tax aggressiveness. The sample used in this study was 105 data of BUMN listed in IDX. The analysis technique used in this study was SEM PLS.The results of this study indicate that capital intensity has a positive effect on tax aggressiveness, while board gender diversity weakens the effect of capital intensity on tax aggressiveness